Gniazdo słowotwórcze wyrazów motywowanych nazwą własną Содом w dyskursie radykalnego ruchu prawosławnego we współczesnej Rosji - Zemszał, Piotr (Studia Rossica Posnaniensia, 2020)
One of the important issues discussed in discourse texts of the radical Orthodox Church movement in Russia is the area of man’s sexual life, including the issue of homosexuality. In the studied texts, resources of nominations referring to sexual orientation and homosexual people are relatively small. The group of lexemes referring to homosexuality, mainly male, most numerously represented in the studied material and most diversified grammatically is the word-formation nest of words motivated by the proper noun Sodom (Содом). The elements of the word-formation nest with the stem содом- are usually used in the text because, due to their significantly axiological character, they make unnecessary the use of other strongly axiological units belonging already to lower stylistic registers. It is also not surprising that in the conservative and Orthodox Church circles the units of biblical origin prevail, and the richness of their forms definitely confirms their current importance in the studied discourse.